2020
DOI: 10.1186/s41239-020-00230-1
|View full text |Cite
|
Sign up to set email alerts
|

The smartphone in self-regulated learning and student success: clarifying relationships and testing an intervention

Abstract: This two-part observational and intervention study addressed the role of the smartphone in self-regulated learning (SRL) and student success as measured by achievement. Smartphone usage among students has been identified as contributing to lower academic achievement in a variety of settings. What is unclear is how smartphone usage contributes to lower outcomes. This study surveyed participants’ self-regulated learning skills and smartphone usage at the beginning and end of the term for first semester undergrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
0
16
1
Order By: Relevance
“…This data's findings further strengthen several previous researchers' claims that self-regulated learning assisted by smartphones is a contributive method of learning. This method can change the way students learn, strengthen the continuity of the learning system, self-evaluate the knowledge and skills they already have, and independently find the correct pattern in meeting the expected learning achievement standards (Aharony & Zion, 2019;Hartley et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This data's findings further strengthen several previous researchers' claims that self-regulated learning assisted by smartphones is a contributive method of learning. This method can change the way students learn, strengthen the continuity of the learning system, self-evaluate the knowledge and skills they already have, and independently find the correct pattern in meeting the expected learning achievement standards (Aharony & Zion, 2019;Hartley et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research into the role of smartphones in the individual learning enterprise has produced some important findings [37,38]. These studies typically investigate how the smartphone hinders learning.…”
Section: Smartphone Use While Studying (Self-regulated Learning)mentioning
confidence: 99%
“…This work is often conceptualized within selfregulated learning theory [40]. Study in this area has found that certain types of smartphone use while studying are closely related to self-regulated learning skills consistent with improved academic achievement [37]. One common measure of self-regulated learning, the Motivated Strategies for Learning Questionnaire (MSLQ), includes components specifically targeting time and effort towards learning [41].…”
Section: Smartphone Use While Studying (Self-regulated Learning)mentioning
confidence: 99%
“…6 In these circumstances online teaching has become the only option left to fulfill the academic necessities of the students though student awareness of the cognitive challenges presented by the smartphone is unclear. 7…”
Section: Introductionmentioning
confidence: 99%